Effectiveness of “Teacher’s Training on Helping Students Learn” on Health Professionals - Shahi, M (Journal of Institute of Medicine Nepal, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Background: The main purpose of this article is to assess the effectiveness of teacher's training workshop through comparing pretest and posttest. Methods: A written 4-point Likert Scale questionnaires was administered to seventy six faculty teachers before and at the end of the teacher's training. The data were collected and analyzed. A descriptive study method was used. Results: Majority of the respondents 68(89.4%) expressed that they can confidently use audiovisual materials such as Flip Chart and Black/White Board effectively during post test while only 26(34.2%) respondents expressed they had some idea of using during pretest. The posttest result reveled highly significant effectiveness of the teacher training programmer's performance in each item. Conclusion: This study demonstrated overall positive effectiveness of the teacher's training workshop. Key words: Pretest, Posttest, Teacher Training Journal of Institute of Medicine, August, 2008; 30:2 39-45 The full text of this paper is available from the Journal of Institute of Medicine website